THE INFLUENCE OF AUDITOR ETHICS, AUDITOR EXPERIENCE AND AUDITOR MOTIVATION ON AUDIT QUALITY AT THE INSPECTORATE OFFICE OF WEST NUSA TENGGARA - Yuli Astini; Agus Khazin Fauzi; Iin Indriani; Endang Kartini (ShariaBiz International Journal of Economics & Business, 2024)
This study examines the effect of auditor ethics, auditor experience, and auditor motivation on audit quality at the Inspectorate Office of West Nusa Tenggara Province (NTB). This research variable consists of 3 (three) independent variables, namely auditor ethics (X1), auditor experience (X2) and auditor motivation (X3), and the dependent variable is audit quality (Y). The population of this study were all auditors at the Inspectorate Office of West Nusa Tenggara Province (NTB). Samples were taken using the saturated sampling method because the population was less than 50. Data were obtained by distributing questionnaires to 35 auditor respondents at the West Nusa Tenggara (NTB) Provincial Inspectorate Office. Thirty-four questionnaires were returned and could be used. Data were analyzed using SPSS 25. The results of this study indicate that auditor ethics and auditor experience affect audit quality. On the other hand, auditor motivation does not affect audit quality. The results of this study also show that the independent variables (auditor ethics, auditor experience, and auditor motivation) can explain the dependent variable by 59.0%. At the same time, other variables influence the remaining 41.0% of audit quality.